On South American spiders previously misplaced in Psilochorus Simon (Araneae: Pholcidae), with the description of a new genus with a remarkable disjunct distribution - Huber, Bernhard A.; Meng, Guanliang; García, Jimmy Cabra (Zootaxa, 2026)
The genus Psilochorus Simon has long been suspected to be an exclusively North American genus, with only one exception: the synanthropic and widely distributed Psilochorus simoni (Berland, 1911). All Old World species and most South American species originally assigned to Psilochorus have been transferred to other genera in the last 25 years. Here we deal with the remaining South American species of “Psilochorus”. Three species from the Brazilian Atlantic Forest are moved to the new genus Lyleka Huber gen. nov.: L. itaguyrussu (Huber, Rheims & Brescovit, 2005) comb. nov. (of which the female is newly described); L. ybytyriguara (Huber, Rheims & Brescovit, 2005) comb. nov.; and L. bromelicola (Huber, 2019) comb. nov.. Two new species from the Colombian Andes are also assigned to this new genus: L. combeima Huber sp. nov., and L. copachi Huber sp. nov. This implies an extremely disjunct distribution of the genus. Based on similar distributions in other taxa, we hypothesize a relatively recent (Miocene) origin of this split, with the Andean uplift as the main driving force. We also document and discuss the unusual conservative evolution of male genitalia in Lyleka: while females have species-specific genitalia, male genitalia tend to be near identical among close relatives. Studies on the sexual biology of Lyleka will be necessary to explain this unusual pattern. Other South American “Psilochorus” are moved to Mesabolivar González-Sponga [M. bruneocyaneus (Mello-Leitão, 1941) comb. nov.; M. sectus (Mello-Leitão, 1939) comb. nov.], to Carapoia González-Sponga [Ca. taperae (Mello-Leitão, 1929) comb. nov.], and to Chibchea Huber [Ch. minima (Schmidt, 1956) comb. nov.]. The latter species was previously known from a single female specimen collected in Hamburg from a shipment of bananas from Ecuador; we redescribe this species based on males and females newly collected in Ecuador. Finally, we present the first records of the synanthropic Psilochorus simoni from South America and Sub-Saharan Africa.